Symbolism of Child Trauma in The Sand Castle - amoer@1, hana prafajarini_1@; Surur, Misbahus (Lingua Cultura, 2025)
The Sand Castle is a film that represents the experience of child trauma in the context of war through subtle visual symbols that are not expressed verbally. The study of child trauma in visual media is important because traumatic experiences at an early age often appear implicitly, thus requiring an interpretive approach to be understood more deeply. This research aims to: (1) identify visual symbols that represent child trauma, (2) analyze the relationship between signifier and signified based on Ferdinand de Saussure's semiotic framework, and (3) explain the function of the imaginative world of child characters as a medium of representation of traumatic experiences. This research uses descriptive-qualitative method with structural semiotic analysis. The research data were selected scenes featuring non-verbal expressions, symbolic objects, and visual atmosphere consistent with the representation of trauma. The selection of data was done purposively, while the analysis was carried out through three stages: identification of sign units, grouping of meanings, and interpretation of sign relationships with psychological contexts. The results show that visual symbols, such as shipwrecks, shadows, and objects belonging to other characters, contain emotional content that represents loss, fear, and hope. In addition, the imaginative world of the child characters is shown to function as a symbolic mechanism to express suffering that is difficult to articulate directly. These findings indicate that film not only presents an aesthetic narrative, but can also be a reflective medium to understand the dynamics of child trauma. Thus, this research contributes to the study of trauma psychology while expanding the perspective of visual media studies on the representation of children's suffering in the context of conflict.